A Meta-Data Analysis on the Primary and Secondary Health Care Needs to Prevent Obesity among the High School Students in the United States - Emmanuel-Janagan, Jessica Evangelin (International Journal of Criminology and Sociology, 2024)
Obesity in schools has grown to become one of the most dramatic features of the global obesity epidemic, with long-term consequences. It has become a public health challenge globally. This study is a meta data analysis of recently published articles in the refereed journals. Fifteen articles were purposively selected based on the criteria of obesity among the high school students and were analyzed to find the recent changing trends of obesity in schools. The analysis of studies demonstrates that school-aged children in the United States have a high prevalence of obesity. The findings provide evidence for prevention intervention strategies to reduce obesity in school-age children. The finding shows that there is a need for more greater awareness of the issues of obesity in schools and the author recommends the ways and means to reduce the obesity in schools in the United States. It is recommended that a healthy lifestyle during high school age is a must for teenagers to avoid obesity.